Efforts to increase the attractiveness of madrasah through improving human resources quality and structuring infrastructure - Irham Nugroho; Eni Kurniawati; Regita Cahyani; Khafifa Choiru Muna; Anna Priastuti (Universitas Muhammadiyah Magelang, 2022)
The attractiveness of madrasa is inseparable from the National Education Standards (SNP) and the measurement results are used as a reference for developing work programs. Two standards that are prioritized for the fulfillment of the eight SNPs are educators and education personnel (HR) and facilities and infrastructure. For this reason, this program is aimed at improving the quality of human resources and infrastructure in order to increase the attractiveness of the community. This program was carried out at MI Muhammadiyah Surodadi 2 Penggaron Hamlet, Gondowangi Village, Sawangan District, Magelang Regency by involving the head of the madrasa and teachers. This program used a participatory rural appraisal approach which is carried out in three stages, namely socialization, training, and mentoring. The result of this program is the increase in HR expertise in graphic design and videography as well as the arrangement of MI facilities and infrastructure.